An Objective, Quantitative Assessment of Flexible Hyaluronic Acid Fillers in Lip and Perioral Enhancement. Issue 5 (May 2021) - Nikolis, Andreas; Bertucci, Vince; Solish, Nowell; Lane, Vanessa; Nogueira, Alessandra
Abstract : BACKGROUND: HARK is an FDA-approved flexible filler designed for lips. OBJECTIVE: To quantitatively evaluate subject outcomes by measuring the change in lip texture, color (redness), lip fullness, and lip and perioral surface stretch (dynamic strain) after treatment. METHODS AND MATERIALS: In this 8-week open-label, Phase IV multicenter study, subjects were treated with HARK in the lips and HARR and/or HARD in perioral wrinkles and folds as add-on treatment. Assessments included 2D photographic analyses of lip texture and color, and 3D photographic assessments of lip enhancement and dynamic strain. RESULTS: HARK significantly improved lip texture ( p ⩽ .002), lip redness ( p < .001), and added fullness to the lips (lip enhancement measurements; p < .001), at Week 8 after treatment. In addition, lower lip wrinkles were significantly reduced ( p = .007) and there was a reduction in upper lip wrinkles (not statistically significant). Surface stretch (dynamic strain) in the lip and perioral region was significantly increased after treatment ( p < .001). CONCLUSION: This analysis provides an objective measure of the beneficial effects of flexible hyaluronic acid fillers in lip augmentation and perioral enhancement and demonstrates a significantly improved lip texture, red color, and fullness. A significant increase in surface stretch (dynamic strain) is indicative of tissue expansion and improvement in lip smoothness. Abstract : Supplemental Digital Content is Available in the Text.